Size distribution and sorption of polychlorinated biphenyls during haze episodes. (January 2018) - Zhu, Qingqing; Liu, Guorui; Zheng, Minghui; Zhang, Xian; Gao, Lirong; Su, Guijin; Liang, Yong
Abstract: There is a lack of studies on the size distribution of polychlorinated biphenyls (PCBs) during haze days, and their sorption mechanisms on aerosol particles remain unclear. In this study, PCBs in particle-sized aerosols from urban atmospheres of Beijing, China were investigated during haze and normal days. The concentrations, gas/particle partitioning, size distribution, and associated human daily intake of PCBs via inhalation were compared during haze days and normal days. Compared with normal days, higher particle mass-associated PCB levels were measured during haze days. The concentrations of ∑PCBs in particulate fractions were 11.9–134 pg/m 3 and 6.37–14.9 pg/m 3 during haze days and normal days, respectively. PCBs increased with decreasing particle size (>10 μm, 10–2.5 μm, 2.5–1.0 μm, and ≤1.0 μm). During haze days, PCBs were overwhelmingly associated with a fine particle fraction of ≤1.0 μm (64.6%), while during normal days the contribution was 33.7%. Tetra-CBs were the largest contributors (51.8%–66.7%) both in the gas and particle fractions during normal days. The profiles in the gas fraction were conspicuously different than those in the PM fractions during haze days, with di-CBs predominating in the gas fraction and higher homologues (tetra-CBs, penta-CBs, and hexa-CBs) concurrently accounting for most of the PM fractions. The mean-normalized size distributions of particulate mass and PCBs exhibited unimodal patterns, and a similar trend was observed for PCBs during both days. They all tended to be in the PM fraction of 1.0–2.5 μm. Adsorption might be the predominating mechanism for the gas-particle partitioning of PCBs during haze days, whereas absorption might be dominative during normal days. Graphical abstract: Highlights: Size distributions of PCBs during haze days and normal days were compared. PM-associated PCB levels were increased during haze days. PCBs exhibited opposite sorption mechanisms in particles during haze and normal days. PCBs were mainly in the 1.0–2.5 μm fraction and presented a unimodal distribution.